The next phase of business ethics integrating psychology and ethics - Dienhart, John William; Moberg, Dennis J., 1944-; Duska, Ronald F., 1937- (JAI, 2001)
In this volume three of the leading scholars in business ethics have arranged a selection of articles examining the intersection of psychology and ethics in relation to organizational concerns. In searching for appropriate business ethics for the 21st century, it is imperative that we continue to embrace a range of inter-related disciplines such as psychology and ethics, but also areas including philosophy, politics, religion, organizational studies, financial and managerial accounting, and many others. This volume serves as an example of interdisciplinary scholarship. In addition, this volume includes articles on religion in business, academic ethics (as an emerging field within organizational ethics), and corporate values in practice.
Keywords: Business ethics.; Organizational behavior -- Moral and ethical aspects.; elektronické knihy; electronic books